Effect of organic, bio-fertilizer and inorganic sources of nutrients on productivity and nutrient status of soil in garden pea based cropping sequence under Lahaul valley of Himachal Pradesh - SHARMA, VISHAL; KALIA, B. D.; RANA1, S. S.; GUPTA, RAHUL (Journal of Soil and Water Conservation, 2021)
A field experiment was carried at the research farm of Highland Agricultural Research and Extension Centre, Kukumseri (Lahaul & Spiti), CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur (Himachal Pradesh) with an objective to evaluate the impact of organic/bio-fertilizer and inorganic sources of nutrients on yield and available nutrient status of soil in garden pea-buckwheat/sarson cropping system. Significant increase was observed in yield attributes such as pods per plant, seeds per pod, green pod yield and straw yield with the application of FYM 2.5 t ha-1 in combination with Rhizobium and the application of 150% or 100% of recommended NPK through chemical fertilizers. This combination also showed a significant improvement in nutrient status of soil in garden pea based cropping system during both the years. Application of FYM 2.5 t ha-1 + Rhizobium found to be significantly better than FYM and Rhizobium alone in influencing yield attributes and yield of pea, and over all nutrient status of the soil. Increase in chemical fertilizers level from 50% to 150% recommended NPK also showed a significantly increase in pea yield and nutrient status of soil during both the years. From the study it can be concluded that for realizing higher yield of pea crop in garden pea based cropping sequence, combination of FYM 2.5 t ha-1 + Rhizobium in integration with 100% of recommended NPK through chemical fertilizers was as good as with 150% of recommended NPK under dry temperate conditions of Lahaul valley.